The Practicality of Self-Study Web-Based Platform of English Proficiency Course at English Department of UNP - Radev Muhammad Aziz; Fitrawati Fitrawati (Journal of English Language Teaching, 2023)
Before implementing a web-based learning platform, it is crucial to assess its practicality. This study aims to know the practicality of the use of self-study web based for the students studying English Proficiency courses at English Department of UNP. Descriptive quantitative research design was used for this study. The respondents in this study were the seven classes of the English Proficiency course offered by the UNP English Department during the academic year 2023. They were given 20 questions to know the practicality of the platform. The results showed that the web-based platform does exceptionally well across the board, gaining a very practical (3.35) use of the product. With usability, accessibility, and adaptability scores of 3.44 (very practical), 3.38 (very practical), and 3.36 (very practical), respectively, it is evident that its design is user-friendly and inclusive, catering to a wide variety of people. The platform excels in relevance and feedback, which are both scored as extremely practical at 3.29 and 3.44, respectively, highlighting its importance in providing contextually suitable material and strong assessment mechanisms. Integration and efficiency are assessed as practical at 3.18 and 3.26. Furthermore, the platform has very practical scores of 3.42 and 3.34 for cost-effectiveness and solid technical support, respectively. All things considered, this web-based platform provides a user-centric, efficient, and successful solution, which makes it a very sensible option for users.